2022
DOI: 10.1038/s41598-022-07076-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction associated with TANGO2 deficiency

Abstract: Transport and Golgi Organization protein 2 Homolog (TANGO2)-related disease is an autosomal recessive disorder caused by mutations in the TANGO2 gene. Symptoms typically manifest in early childhood and include developmental delay, stress-induced episodic rhabdomyolysis, and cardiac arrhythmias, along with severe metabolic crises including hypoglycemia, lactic acidosis, and hyperammonemia. Severity varies among and within families. Previous studies have reported contradictory evidence of mitochondrial dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…ROS produced as a byproduct of ATP synthesis is useful for cells, but high levels of ROS unless scavenged are toxic. The fact that TANGO2 localizes to mitochondria and an earlier report of an increased in mitochondrial-ROS in cells from TANGO2 deficiency patients 5 prompted us to test this feature in our experimental conditions. TANGO2 depleted cells with 10% FBS (DMEM complete), or without FBS (Starvation), and mock cells were incubated for 20 min with CellROX Deep Red reagent to measure cellular ROS levels and MitoTracker Green to measure total mitochondrial mass by flow cytometry analysis.…”
Section: Tango2 Depleted Cells Exhibit High Levels Of Reactive Oxygen...mentioning
confidence: 89%
See 1 more Smart Citation
“…ROS produced as a byproduct of ATP synthesis is useful for cells, but high levels of ROS unless scavenged are toxic. The fact that TANGO2 localizes to mitochondria and an earlier report of an increased in mitochondrial-ROS in cells from TANGO2 deficiency patients 5 prompted us to test this feature in our experimental conditions. TANGO2 depleted cells with 10% FBS (DMEM complete), or without FBS (Starvation), and mock cells were incubated for 20 min with CellROX Deep Red reagent to measure cellular ROS levels and MitoTracker Green to measure total mitochondrial mass by flow cytometry analysis.…”
Section: Tango2 Depleted Cells Exhibit High Levels Of Reactive Oxygen...mentioning
confidence: 89%
“…Previous published data revealed the location of TANGO2 to mitochondria in cells and in mitochondrial enriched membranes 2,5 . But this has also been challenged 6 .…”
Section: Tango2 Localizes Predominantly To the Mitochondria But Also ...mentioning
confidence: 95%
“…Proteomic analysis of fibroblasts from TANGO2 patients revealed significant changes in the component of mitochondrial fatty acid oxidation, plasma membrane, endoplasmic reticulum, Golgi and secretory pathway indicating pleiotropic roles in disease biology (Mingirulli et al, 2020). Some patients’ fibroblasts also showed a defect in palmitate-dependent oxygen consumption suggestive of impaired mitochondrial fatty acid oxidation (Heiman et al, 2022; Kremer et al, 2016). In contrast, myoblasts from TANGO2 patients exhibit no defects in mitochondrial structure and function but exhibit abnormalities in mitochondrial function under nutrient stress suggesting the involvement of extrinsic factors in inducing cellular defects (Bérat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The latter molecule is a cofactor required in a number of cellular processes, perhaps best known as an electron acceptor/donor in energy production in the mitochondria. Given that several studies have suggested that a portion of the TANGO2 protein associates with mitochondria in humans and mice 7, 9, 29 , and a mitochondrial defect may be a secondary consequence of TANGO2 deficiency, the modest benefit of vitamin B3 in the climbing assay may reflect a non-specific overall increase in energy production or other factors, such as mitigation of oxidative stress. Consistent with this notion, vitamin B3 has been shown to be beneficial in a number of different, unrelated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3, 6, 7, 8 Several reports have shown defective endomembrane trafficking and dilated endoplasmic reticulum (ER) in fibroblasts derived from TDD affected individuals. 3, 7 Other studies have demonstrated defective mitochondrial morphology and respiration 3, 7, 9 leading to the speculation that TANGO2 may affect some as yet unknown aspect of lipid metabolism One study reported abnormal palmitate oxidation in cells derived from two individuals harboring two different TANGO2 alleles, suggesting a defect in fatty acid oxidation and/or oxidative phosphorylation. 2 These various results have made it difficult to devise treatment options for affected individuals, particularly to avoid the metabolic crisis which is the sole contributor of TDD lethality.…”
Section: Introductionmentioning
confidence: 99%